A preliminary assessment of longitudinal amyloid status in the ongoing open‐label extension phase in subjects with early Alzheimer's disease: Human/Human trials: Anti‐amyloid. (7th December 2020) - Swanson, Chad J.; Zhang, Yong; Dhadda, Shobha; Wang, Jinping; Kaplow, June; Bradley, Heather; Rabe, Martin; Lai, Robert Y.K.; Gordon, Robert; Kramer, Lynn D.
Abstract: Background: BAN2401 is a humanized IgG1 monoclonal antibody that selectively binds large soluble Aβ aggregates over monomers and fibrils. We have previously shown that amyloid reduction over 18 months of BAN2401 treatment at 10 mg/kg‐biweekly persists at baseline in an open label extension (OLE) following long‐term withdrawal from BAN2401. Here, we present preliminary data on the early longitudinal effects of BAN2401 on brain amyloid in the OLE of BAN2401‐G000‐201. Methods: Subjects who fulfilled OLE inclusion/exclusion criteria were eligible. Amyloid positivity was required at baseline of the core Phase 2 study. Amyloid PET status was determined by visual read using an identical approach to that conducted at baseline in the core. The OLE was initiated after analysis of the core study showed clinical potential for BAN2401, thus, individuals were off drug for variable periods of time prior to entering the OLE. All subjects received 10 mg/kg biweekly in the OLE. Data for longitudinal PET standard uptake value ratio (SUVr) were collected in subjects at either 3mo and 6mo assessment. Piecewise regression was used to predict change from OLE baseline over 6mo. Results: A total of 105 subjects from the core study have undergone an amyloid PET at OLE baseline with florbetatpir (mean duration off drug: ∼24mo; min=9.2mo; max=59.7mo). OLE baseline SUVr for those with longitudinal OLE assessments in the core phase for placebo, 10mg/kg‐monthly, and 10mg/kg‐biweekly were 1.46 (N=5), 1.21 (N=7), and 1.09 (N=8), respectively. Mean PET SUVr change from OLE baseline at 6mo was ‐0.26 (N=5), ‐0.09 (N=7), and ‐0.01 (N=8), with predicted slopes for 6 mo change of ‐0.042, ‐0.012, and ‐0.005 for subjects treated in the core phase with placebo, 10mg/kg‐monthly, and 10mg/kg‐biweekly, respectively. Three (3) of 5 subjects in the core placebo group became amyloid negative by visual read at 3mo treatment in OLE, with 5/5 subjects amyloid negative at 6mo. Conclusions: In this preliminary analysis, 10 mg/kg‐biweekly BAN2401‐mediated amyloid reduction in the OLE was dependent on core treatment/SUVr at OLE baseline, and was apparent by 3mo with amyloid negativity achieved at 6mo (visual read) in placebo‐treated subjects from the core. Updated data will be presented as available.